Portrayals of identity in the romanser and reception of Ture Rangström - Macgregor, Anne (2017)
This thesis offers the first in-depth study of the Swedish composer Ture Rangström (1884-1947) in English-language scholarship. Although Rangström is well known in Sweden, particularly for his sizable contribution to the art-song genre, his music is still unfamiliar on the international stage. This thesis considers the composer and his songs in their immediate context of early twentieth-century Stockholm, but also in relation to broader trends in pan-European musical developments, with a particular focus on issues of nationalism and modernism and the distinctive ways in which these were articulated in Swedish culture. In a series of case studies, songs drawn from across Rangström’s career are examined as musical expressions of Sweden’s literature, language, and landscape, and as a means of forming and conveying the composer’s sense of self. This thesis also corrects misrepresentations that have dominated Rangström’s reception and explores strategies for approaching the writings both by and about him that have been shaped by his habit of deliberate self-presentation.